2008
DOI: 10.1364/ol.33.001917
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-temperature regenerated gratings in boron-codoped germanosilicate optical fiber using 193 nm

Abstract: Regenerated gratings seeded by type I gratings in boron-codoped germanosilicate optical fiber written with 193 nm are shown to withstand temperatures beyond 1000 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 11 publications
7
105
4
Order By: Relevance
“…This chirp is an exaggerated copy of the seed grating quadratic chirp so the complex profile of the seed grating was preserved. When tension is removed during regeneration, B is the same between seed and regenerated grating, also consistent with our previously reported observations [Bandyopadhyay et al 2008;Canning et al 2008b]. Fig.…”
Section: Fabrication Of Regenerated Gratingssupporting
confidence: 91%
See 4 more Smart Citations
“…This chirp is an exaggerated copy of the seed grating quadratic chirp so the complex profile of the seed grating was preserved. When tension is removed during regeneration, B is the same between seed and regenerated grating, also consistent with our previously reported observations [Bandyopadhyay et al 2008;Canning et al 2008b]. Fig.…”
Section: Fabrication Of Regenerated Gratingssupporting
confidence: 91%
“…In practice, we have confirmed that the stronger the seed grating, the stronger the final regenerated grating. For this case, a conventional Bragg grating inscribed into hydrogen loaded (24hrs, 200atm, 70°C) relatively highly germanium doped step index fibre with no boron (r core ~ 2μm, [GeO 2 ~ 10.5mol%], Δn co/cl = 0.012), using the 244nm output from a frequency doubled Ar + laser (P ~ 50W/cm 2 , f cumulative ~ (6-12)kJ/cm 2 , the same as that reported in Bandyopadhyay et al 2008 andCanning et al 2008b). Figure 6 shows the transmission and reflection of a very strong type I Bragg grating, readily exceeding the noise floor in transmission of our tunable laser and power meter setup (res: 1pm).…”
Section: Fabrication Of Seed Gratingsmentioning
confidence: 96%
See 3 more Smart Citations